Increased self disclosure and self adjustment through group counseling with a person centered approach of students - K, Fatmah (COUNS-EDU: The International Journal of Counseling and Education)
This research is motivated by self-disclosure and adjustment of some students on XI grade class of Madrasah Aliyah Madania Bantul Yogyakarta which is quite low. This study aims to improve self-disclosure and self-adjustment of learners through group counseling with a person centered approach This research uses the type of action research conducted in three cycles using Kemmis and Taggart model. Each cycle consists of four stages, planning, action, observation and reflection. The subjects of this study are students on Xi grade class of Madrasah Aliyah Madania Bantul Yogyakarta who have low self-disclosure and self-adjustment that amounted to 5 people. The results showed that group counseling with person centered approach can improve self-disclosure and adaptation students of grade XI in Madrasah Aliyah Madania Bantul Yogyakarta. This increase has been proven through research in each group, namely: (1) in group A, the number of subjects who have high self-disclosure in the 1st cycle is 40%, and getting increased in 2nd cycle to 80%, while the number of subjects who have high self-adjustment in 1st cycle is 40%, in 2nd cycle is 60%, and getting increased in 3rd cycle to 80%. (2) in group B the number of subjects who have high self-disclosure in 1st cycle is 20%, 2nd cycle is 40% and getting increased in 3rd cycle to 80%, while for the number of subjects who have adjusted in the cycle is 40%, 60% and increased in 3rd cycle as much as 80%. The results are also reinforced through observations that show that learners have been able to communicate, express themselves and fit in well. From the interviews, learners admit that group counseling activities can improve the ability to express themselves, adjust to other people and feel helpful in solving problems.